SERVICE QUALITY AND ONLINE CUSTOMER RATING ON F&B PURCHASE DECISIONS - Ahmad Dzul Ilmi Syarifuddin (Jurnal Riset Bisnis dan Manajemen, 2022)
This study aims to determine how the influence of service quality and online customer rating on food and beverage product purchasing decisions using the Grabfood application. This research data is sourced and collected from questionnaires distributed to respondents (consumers Grabfood application). The number of respondents in this study amounted to 100 respondents in Makassar. This type of research is a quantitative research. The research method uses multiple linear regression analysis using SPSS software to process the data. The results showed that Service Quality had a positive and significant effect on Purchase Decisions, Online Customer Rating had a positive and significant effect on Purchase Decisions, Service Quality and Online Customer Rating simultaneously had a positive and significant effect on Purchase Decisions.